Market orientation and the property development business in Singapore - Tay, Jasmine Y.W.; Tay, Linda (International Journal of Strategic Property Management, 2010)
The property development business is often regarded as one of high risk and return. As such, developing a competitive advantage is critical. Extant literature suggests that market orientation is a form of sustainable competitive advantage for businesses. This paper is an attempt to test this relationship with specific reference to a high risk business such as property development. A market orientation scale is developed to measure the degree of market orientation in property development firms. The results show that there exists a significant positive relationship for two specific dimensions of market orientation, i.e., profit orientation and responsiveness with business performance and marketing performance. Furthermore, empirical findings showed that the relationship between market orientation and marketing performance was stronger than with business performance. First published online: 18 Oct 2010